PELAKSANAAN PRINSIP FIRST TO FILE DALAM PENYELESAIAN SENGKETA MEREK DAGANG ASING DI PENGADILAN (Studi Kasus tentang Gugatan Pencabutan Hak Merek “TOAST BOX” oleh BreadTalk Pte.Ltd No: 02/Merek/2011/PN.Niaga/Medan) - VANIA ISURA SITEPU (PREMISE LAW JURNAL, 2015)
The registration of trademark done by the Directorate General of Intellectual PropertyRights was intended to obtaine legal certainty and legal protection for the right to trademark in accordance with Law No.15/2001. The registration of trademark through constitutive system (First to File) more guarantees the existence of legal certainty for the holder of right to trademark because the one who registered the trademark was given a certificate as a proof of registration and a proof of right to trademark, and at the same time, the registrant is reagarded as the first user of the trademark. The settlement of dispute on Foreign Trademark which is principally or wholly similar to the registered trademark can be carried out based on the civil, criminal and administrative approach. In terms of legal protection, in relation to the existing cases of trademark, legal protection that can be given to the owner of the registered trademark is to file a lawsuit on the cancellation of brand (trademark) considering the constitutive system followed by the Indonesian Law on Brand (Trademark) saying that legal protection is given to the first registrant of trademark. It is expected that the process of trademark registration can be simplified and shortened and the data system and publication of the Directorate General of Intellectual PropertyRights should be improved that the business practitioners will be not in doubt to register their trademarks. To give more legal protection to the holders of foreign trademarks, harmonious cooperation is needed between the government accompanied with adequate regulations of legislation, brand (trademark) inspection apparatuses (the Directorate General of Intellectual PropertyRights), law enforcement officers, community members at large in announcing the information about violation brands and entrepreneurs who will use a particular brand for their products. That, in practice, the First to File registration system can be effectively run and create the alignment of guarantees justice and expediency, because there many brands (trademarks) registered not by their actual owners. Kata Kunci: Brand (Trademark), First to File Principle